Menangkal hoax melalui workshop literasi media dan bedah film “Tilik” bagi Karang Taruna Desa Karyamekar - Chotijah Fanaqi; Arti Nurdianti Chairunnisa (Penerbit Goodwood, 2020)
Purpose: The aim of the media literacy workshop through the review of the Tilik film is to build awareness and understanding for Karyamekar associations in an effort to ward off hoaxes that are rife on social media. The discussion and review of this film was in the context of the implementation of Community Service which was held by the Garut University Service Team in collaboration with the Youth Organization of Karyamekar Village, Cilawu District, Garut Regency. Method: The method used is a workshop and film surgery